Worldwide Research Trends in the Recycling of Materials - Manzano-Agugliaro, Francisco; Salmerón-Manzano, Esther; Alcayde, Alfredo; Garrido-Cardenas, José Antonio (Encyclopedia of Renewable and Sustainable Materials: Volume 1-5, 2023)
This study examines global research on the subject of recycling in the category of materials. For this purpose, a bibliometric research has been carried out in the Scopus database. All the records obtained have been used and analyzed in the following fields: The worldwide evolution of scientific production index of the research maturity; the indexation categories; the main sources where these works were published; carrying out an analysis of quality indicators; the main countries and institutions dealing with this subject; and the main keywords associated with this subject. Finally, a study is made of the scientific communities or clusters around which all these world publications are grouped and how they relate to each other. Eight clearly differentiated communities or clusters have been detected that represent 99.7% of worldwide research in this field: Plastics (34.9%), concrete (18.6%), rubbers (11.8%), aluminum (9.9%), blast furnace (9.1%), batteries (7.7%), paper (4.23), and wastewater (3.5).
Keywords: aluminum; batteries; blast furnace; community detection paper; concrete; plastics; recyclability; renewability; rubbers; wastewater; worldwide research; Scopus